E2-EPF UCP regulates stability and functions of missense mutant pVHL via ubiquitin mediated proteolysis. Issue 1 (December 2015) - Park, Kyeong-Su; Kim, Ju; Shin, Hee; Chung, Kyung-Sook; Im, Dong-Soo; Lim, Jung; Jung, Cho-Rok
Abstract Background Missense mutation ofVHL gene is frequently detected in type 2 VHL diseases and linked to a wide range of pVHL functions and stability. Certain mutant pVHLs retain ability to regulate HIFs but lose their function by instability. In this case, regulating of degradation of mutant pVHLs, can be postulated as therapeutic method. Method The stability and cellular function of missense mutant pVHLs were determine in HEK293T transient expressing cell and 786-O stable cell line. Ubiquitination assay of mutant VHL proteins was performed in vitro system. Anticacner effect of adenovirus mediated shUCP expressing was evaluated using ex vivo mouse xenograft assay. Results Three VHL missense mutants (V155A, L158Q, and Q164R) are directly ubiquitinated by E2-EPF UCP (UCP) in vitro. Mutant pVHLs are more unstable than wild type in cell. Missense mutant pVHLs interact with UCP directly in both in vitro and cellular systems. Lacking all of lysine residues of pVHL result in resistance to ubiquitination thereby increase its stability. Missense mutant pVHLs maintained the function of E3 ligase to ubiquitinate HIF-1α in vitro. In cells expressing mutant pVHLs, Glut-1 and VEGF were relatively upregulated compared to their levels in cells expressing wild-type. Depletion of UCP restored missense mutant pVHLs levels and inhibited cell growth. Adenovirus-mediated shUCP RNA delivery inhibited tumor growth in ex vivo mouse xenograft model. Conclusion These data suggest that targeting of UCP can be one of therapeutic method in type 2 VHL disease caused by unstable but functional missense mutant pVHL.